Preventing Cyber Crime Through Awareness, Use of Technology and Facilitating Conditions: Theory of Planned Behavior Perspective - Prihanto, Hendi; Usmar; Damayanti, Prisila (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The increasing reliance on digital technology has simultaneously escalated the frequency and sophistication of cybercrime, posing serious risks to financial stability, data security, and organizational performance. This condition underscores the urgent need for effective prevention strategies that combine user awareness, technological adoption, and supportive facilitating conditions. The study aims to analyze factors that influence cybercrime prevention, including user awareness of the dangers of cybercrime and its prevention, the use of information technology, and facilitating conditions towards cybercrime prevention in Indonesia. The study was conducted using quantitative methods through a series of primary data tests obtained using questionnaires, with respondents being users of cloud-based information technology systems, such as private companies and banks, in 2025. Data processing was carried out using SEM-PLS media with a series of inner and outer model feasibility tests before regression and hypothesis testing were carried out. The results of the study stated that all observed variables that were predicted to influence the effectiveness of cybercrime prevention, namely awareness, use of information technology, and facilitating conditions, had a positive and significant effect on cybercrime prevention.